2011
DOI: 10.1371/journal.pone.0025797
|View full text |Cite
|
Sign up to set email alerts
|

H3N2 Influenza Infection Elicits More Cross-Reactive and Less Clonally Expanded Anti-Hemagglutinin Antibodies Than Influenza Vaccination

Abstract: BackgroundDuring the recent H1N1 influenza pandemic, excess morbidity and mortality was seen in young but not older adults suggesting that prior infection with influenza strains may have protected older subjects. In contrast, a history of recent seasonal trivalent vaccine in younger adults was not associated with protection.Methods and FindingsTo study hemagglutinin (HA) antibody responses in influenza immunization and infection, we have studied the day 7 plasma cell repertoires of subjects immunized with seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
175
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(190 citation statements)
references
References 56 publications
14
175
0
1
Order By: Relevance
“…In total, our analysis of the CCH rabbit revealed that the antigen-specific polyclonal response is composed of ∼34 IgG antibodies that are classified into 30 different clonotypes [same V and J, same CDRH3 length, 80% aa homology (14,15)]; 4 of the 34 antibodies that constitute the majority of the antigen-specific IgG repertoire in this animal differed by only 1-3 aa and therefore corresponded to clonally related antibodies ( Fig. 3B; also SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In total, our analysis of the CCH rabbit revealed that the antigen-specific polyclonal response is composed of ∼34 IgG antibodies that are classified into 30 different clonotypes [same V and J, same CDRH3 length, 80% aa homology (14,15)]; 4 of the 34 antibodies that constitute the majority of the antigen-specific IgG repertoire in this animal differed by only 1-3 aa and therefore corresponded to clonally related antibodies ( Fig. 3B; also SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Composed of the V(D)J join with its inherent junctional diversity, the CDRH3 specifies the V H clonotype. The V H clonotype is defined as the group of V H sequences that share germ-line V and J segments, have identical CDRH3 lengths, and exhibit greater than 80% amino acid identity in the CDRH3 sequences (14,15). The V H clonotype is an important immunological concept because it accounts for antibodies that likely originate from a single B-cell lineage and may provide insight on the evolution of the antigenspecific response of that lineage.…”
Section: Resultsmentioning
confidence: 99%
“…The V H repertoires for each donor, encoded by day 7 plasmablasts and by IgD − mBCs collected on both day 7 and 3 mo postboost, were determined by 454 (Roche Diagnostics GmbH) sequencing (70,326 and 157,089 high-quality V H reads for HD1 and HD2, respectively; Table S1) and indexed by their V H clonotype. The V H clonotype, which represents a cluster of antibodies that likely originate from a single B-cell lineage (27,28), is defined here as the group of V H sequences that share germ-line V and J segments and also exhibit greater than 90% amino acid identity in the complementarity-determining region (CDR)-H3 (threshold for CDR-H3 amino acid identity determined by analysis of test sets from clustered deep-sequencing data; Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…The mean heavy chain mutation frequency was 4.00 % ± 1.61 % (range 1.72-6.16 %), a mutation frequency typical of antibodies isolated from vaccine recipients [46,47]. None of the recovered mAbs were clonally related to each other, and a range of VH genes was used (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%